The Pharmacology of Anxiolytics - Kim Outhoff (South African Family Practice)
Given that anxiety disorders are common and chronic and often co-morbid with both medical and psychiatric conditions, effective and safe anxiolytic drugs are in great demand. Serotonergic agents, in particular the selective serotonin reuptake inhibitors and serotonin and noradrenaline reuptake inhibitors, have an established track record for the pharmacological treatment of a wide range of anxiety disorders. Despite their slow onset of therapeutic action, their initial exacerbation of anxiety and some of their long-term unwanted effects, they remain the drugs of first choice in primary care. They are relatively safe and exhibit both anxiolytic and antidepressant effects. Other antidepressants, such as mirtazapine, reboxetine and agomelatine, and the 5-HT1A agonist, buspirone, are alternative agents, although the evidence of their efficacy covers a narrower spectrum of anxiety disorders. Patients with anxiety disorders who are resistant to these drugs may benefit from second-line (tricyclic antidepressants or monoamine oxidase inhibitors) or even specialist initiated thirdline (benzodiazepine, anticonvulsant or antipsychotic) therapy. None of the currently available drugs are ideal for every patient and the advantages and disadvantages of each are best considered when treatment is individualised.